Edukasi Dan Pengenalan Akad-Akad Dalam Ekonomi Syariah Pada Santri Ppmti Tanjung Berulak Kec. Kampar - Zakir, Muhammad; Mairiza, Diany; Khairi, Rifqil; Rahmawati, Rahmawati; Amelia, Nur; Lismawati, Lismawati (EL-EMIR INSTITUTE, 2025)
This community service program aims to introduce the concepts of contracts (akad) in Islamic economics to the students of Pondok Pesantren Madrasah Tarbiyah Islamiah (PPMTI) Tanjung Berulak as a solution for Islamic financial management. The material was delivered through a lecture method, providing the students with content relevant to the theme. After the presentation, a discussion session was conducted, giving the students an opportunity to ask questions related to the topic, allowing them to explore the concepts more deeply. The results of this activity show an increase in the students’ understanding of the importance of Islamic financial management, as well as their enthusiasm for applying Islamic financial principles in their daily lives. This program is expected not only to provide direct benefits to the students but also to inspire them to become agents of change in their communities, promote Islamic finance, and support the creation of a more Islamic and prosperous society.